Europa Universalis IV and Deep Learning: Historical Accuracy, Counterfactuals and Historical Themes - Loban, Rhett (Loading, 2021)
This article examines issues encountered with Europa Universalis IV (EUIV) in terms of teaching history in adult learning. The article identifies the educational limitations of the game, as well as the types of history that can be learnt from it. The data collected from participant responses is examined in terms of an ongoing concern regarding the balancing of historical accuracy and gameplay in EUIV. In this discussion about balance, participants raise common concerns about the historical abstraction, historical misinformation and counterfactual elements within EUIV. Nonetheless, the article argues that despite these ahistorical elements, EUIV can still potentially portray many of history’s larger trends and influences. Given the portrayal of these trends in-game, the article examines the pedagogical utility of the game in terms of narrative engagements with history and the promotion of deeper forms of learning.